Effect of Arsenic Amended Irrigation Water on Growth and Yield of BR-11 Rice (Oryza sativa L.) Grown in Open Field Gangetic Soil Condition in Rajshahi - Azad, MAK; Mondal, AHMFK; Hossain, MI; Moniruzzaman, M (Journal of Environmental Science and Natural Resources, 2012)
Rice was grown in an open-field Gangetic soil condition with arsenic amended irrigation water in experimental plot at Institute of Environmental Science of Rajshahi University to see the effect of arsenic (As) on growth and yield of rice (Oryza sativa L.). A popular aman rice variety named BR-11 was cultivated with arsenic amended irrigation water (0 mg, 0.1 mg, 0.5 mg, 1.0 mg, 2.0 mg and 4.0 mg/L As containing water) in a green house made of transparent poly-ethylene paper. Sodium arsenate (Na2HAsO4) was added to irrigation water for arsenic source. The tillers number, panicle length and grain yield of BR-11 rice were found to decrease significantly (p?0.05) with increase of arsenic (As) concentration in irrigation water. The highest values of plant height and straw yield was observed in 0.5 mgL-1 treatment, whereas highest tillers number, panicles number, panicle length and grain yield were found in control treatment. The lowest values of these parameters were observed in the treatment of 4.0 mgL-1 As containing irrigation water. Rice was grown in an open-field Gangetic soil condition with arsenic amended irrigation water in experimental plot at Institute of Environmental Science of Rajshahi University to see the effect of arsenic (As) on growth and yield of rice (Oryza sativa L.). A popular aman rice variety named BR-11 was cultivated with arsenic amended irrigation water (0 mg, 0.1 mg, 0.5 mg, 1.0 mg, 2.0 mg and 4.0 mg/L As containing water) in a green house made of transparent poly-ethylene paper. Sodium arsenate (Na2HAsO4) was added to irrigation water for arsenic source. The tillers number, panicle length and grain yield of BR-11 rice were found to decrease significantly (p?0.05) with increase of arsenic (As) concentration in irrigation water. The highest values of plant height and straw yield was observed in 0.5 mgL-1 treatment, whereas highest tillers number, panicles number, panicle length and grain yield were found in control treatment. The lowest values of these parameters were observed in the treatment of 4.0 mgL-1 As containing irrigation water. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11553 J. Environ. Sci. & Natural Resources, 5(1): 55-59, 2012